Healthcare burden of recurrent Clostridioides difficile infection in Japan: A retrospective database study. Issue 11 (November 2018) - Kunishima, Hiroyuki; Ito, Kaoru; Laurent, Thomas; Abe, Machiko
Abstract: This retrospective database study aimed to assess the healthcare burden of hospitalization cost and duration associated with recurrent Clostridioides difficile infection (rCDI) by comparison with C . difficile infection (CDI) in Japan, using a health claims database of 270 acute care hospitals. Overall, 5423 hospitalized patients, with a record of one hospital-onset, healthcare facility-associated primary CDI episode within the 180-day period, from its onset between January 2012 and September 2016, were included. Of these, 353 had at least one rCDI and 5070 had no rCDI. Compared with those with no rCDI, the median total cost of hospitalization for patients with rCDI was JPY 1, 184, 371 (USD 11, 691) higher (JPY 2, 489, 424 [interquartile range IQR: 1, 597, 424–4, 008, 751] compared with JPY 1, 305, 053 [624, 033–2, 549, 569]). In addition, rCDI resulted in twice longer hospitalization duration in median compared with CDI (79 days [IQR: 53–117] compared with 40 days [20–74]). Based on a generalized linear regression model with a Gamma distribution and a logarithmic link function, the estimated mean of cost and duration of hospitalization for patients with rCDI were JPY 1, 284, 519 (95% confidence limit: −95, 532–2, 664, 569) (USD 12, 679) higher and 20.3 days (−9.5‒50.0) longer, compared with patients with no rCDI. The estimated mean difference in cost was higher in older patients and patients with diseases resulting in an immunosuppressive state. Higher costs and longer hospitalization for rCDI impose a great burden on healthcare system as well as patients, highlighting the importance of preventing recurrence of CDI.